2014
DOI: 10.1177/1938965514551633
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ Perspectives about Employing People with Disabilities

Abstract: A comparison of managerial hiring intentions and attitudes toward people with disabilities between service businesses and goods-producing industries found that service firms are more likely to recruit people with disabilities. Based on a comparison of 263 leisure and hospitality companies with 3,126 firms in other industries, service-producing industries are more likely to actively recruit workers with disabilities when compared with goods-producing companies. Customer attitudes toward people with disabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 23 publications
1
48
0
1
Order By: Relevance
“…These studies found larger, public‐sector, unionized, and service organizations were associated with increased employment of persons with disabilities. These types of organizations were also associated with positive responses toward persons with disabilities, such as changing work systems, providing accommodations, and providing special training (Bruyère et al, ; Dong, Oire, MacDonald‐Wilson, & Fabian, ; Goss et al, ; Harcourt et al, ; Hernandez et al, ; Houtenville & Kalargyrou, ; Lee, ; Morgan & Alexander, ; Richards & Sang, ; Woodhams & Corby, ). Goss et al () suggested that the organizational size is a proxy for having specialized HR managers who can learn about best practices in disability management through professional associations, which can encourage them to develop better practices for disability employment.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 99%
“…These studies found larger, public‐sector, unionized, and service organizations were associated with increased employment of persons with disabilities. These types of organizations were also associated with positive responses toward persons with disabilities, such as changing work systems, providing accommodations, and providing special training (Bruyère et al, ; Dong, Oire, MacDonald‐Wilson, & Fabian, ; Goss et al, ; Harcourt et al, ; Hernandez et al, ; Houtenville & Kalargyrou, ; Lee, ; Morgan & Alexander, ; Richards & Sang, ; Woodhams & Corby, ). Goss et al () suggested that the organizational size is a proxy for having specialized HR managers who can learn about best practices in disability management through professional associations, which can encourage them to develop better practices for disability employment.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 99%
“…Employers' pervasive negative views about the work productivity of people with disabilities are mentioned in several studies, along with employers' lack of knowledge concerning disabilities and accommodation strategies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…PWD are very loyal and committed employees and change jobs less often, reducing staff turnover. In addition, PWD are an integral part of a diverse workforce (Houtenville and Kalargyrou, 2015). Psychological work safety seems to be increased by the competitive employment of PWD, which can lead to higher motivation of all employees, less personnel fluctuation, higher overall profitability, and results in a competitive advantage (Kalargyrou, 2014).…”
Section: Resources and Skills Through The Employment Of Pwdmentioning
confidence: 99%